1990
DOI: 10.1080/10862969009547707
|View full text |Cite
|
Sign up to set email alerts
|

A Semiotic Perspective of Text: The Picture Story Book Event

Abstract: The focus of this paper is on the exploration of the nature of the picture story book event from a semiotic perspective. One purpose of the study was to examine how pictures and words relate in picture books. A second purpose was to explore how one picture story book was constructed during teacher-student-text interaction in a second-grade classroom. The classroom event involved an oral reading and discussion of the text, interpretations of the main character's traits, letters to the author, and illustrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 9 publications
2
14
0
Order By: Relevance
“…Findings of this study also confirm other research that have investigated children's reading of picture books (Golden & Gerber, 1990;Meek, 1998;Stephens, 1990, Lewis 2001Fueyo, 1991). Both studies on wordless picture books and picture books indicate children rely on many of the same strategies for reading wordless, visual texts, as they do when reading texts that offer a combination of print and visual texts (Crawford & Hade, 2000).…”
Section: Discussionsupporting
confidence: 80%
“…Findings of this study also confirm other research that have investigated children's reading of picture books (Golden & Gerber, 1990;Meek, 1998;Stephens, 1990, Lewis 2001Fueyo, 1991). Both studies on wordless picture books and picture books indicate children rely on many of the same strategies for reading wordless, visual texts, as they do when reading texts that offer a combination of print and visual texts (Crawford & Hade, 2000).…”
Section: Discussionsupporting
confidence: 80%
“…As well, several families traced the length of the eel in an illustration, with a finger to emphasise, and kinaesthetically demonstrate, its size. Interestingly, the Prentice child used tone of voice to signal the concept of size paralinguistically (Golden & Gerber, 1990 One, two, three, four, five .... twenty-one, twenty-two, twenty-three (looks at her mother) M: Twenty-three minutes long? (laughs) That's a very long eel.…”
Section: Fmentioning
confidence: 99%
“…Proponents of children's literature have long argued that images are a crucial part of the text (Genette, 1997;Golden & Gerber, 1990;Higgonet, 1990), and research has suggested that children use verbal and visual information to construct meaning (Duckett, 2001;Hannus & Hyönä, 1999;. This study, through the use of both oral reading and eye tracking, not only documents that children make use of the relationship between the verbal and visual texts, but also helps to clarify factors that influence children's use of images.…”
Section: Discussionmentioning
confidence: 99%